Integrasi Pasar Jagung di Indonesia - Maya Puspita Sari; Yosini Deliana; Dini Rochdiani (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2021)
Corn commodity has a strategic role whose demand continues to increase for industrial needs, especially the animal feed industry. The high fluctuations in corn prices occur because a balanced supply has not accompanied the increasing demand for corn. The study aimed to analyze the integration of the maize market at the feed mill level with the maize market at the farmer and global levels. The method used is quantitative with secondary data. Data analysis using Vector Error Correction Model (VECM). The results show that the corn market in the long term at the feed mill level is integrated with the corn market at the farmer and global levels. However, only corn markets at the farmer level are integrated with feed mills in the short term.Komoditas jagung memiliki peranan strategis yang permintaannya terus meningkat untuk kebutuhan industri, khususnya industri pakan ternak. Fluktuasi harga jagung yang tinggi terjadi karena permintaan jagung yang meningkat belum diiringi dengan penawaran yang seimbang. Tujuan penelitian untuk menganalisis integrasi pasar jagung di tingkat pabrik pakan dengan pasar jagung di tingkat petani dan dunia. Metode yang digunakan adalah kuantitatif dengan data sekunder. Analisis data menggunakan Vector Error Correction Model (VECM). Hasil penelitian menunjukan bahwa pasar jagung dalam jangka panjang di tingkat pabrik pakan terintegrasi dengan pasar jagung di tingkat petani dan dunia. Namun, dalam jangka pendek hanya pasar jagung di tingkat petani yag terintegrasi dengan pabrik pakan.